Dietary Restriction Promotes Vessel Maturation in a Mouse Astrocytoma - Urits, Ivan (Hindawi Publishing Corporation, 2012)
Mature vasculature contains an endothelial cell lining with a surrounding sheath of pericytes/vascular smooth muscle cells (VSMCs). Tumor vessels are immature and lack a pericyte sheath. Colocalization of vascular endothelial growth factor receptor 2 (VEGFR-2) and platelet-derived growth factor receptor beta (PDGF-Rβ) reduces pericyte ensheathment of tumor vessels. We found that a 30% dietary restriction (DR) enhanced vessel maturation in the mouse CT-2A astrocytoma. DR reduced microvessel density and VEGF expression in the astrocytoma, while increasing recruitment of pericytes, positive for alpha-smooth muscle actin (α-SMA). Moreover, DR reduced colocalization of VEGF-R2 and PDGF-Rβ, but did not reduce total PDGF-Rβ expression. These findings suggest that DR promoted vessel normalization by preventing VEGF-induced inhibition of the PDGF signaling axis in pericytes. DR appears to shift the tumor vasculature from a leaky immature state to a more mature state. We suggest that vessel normalization could improve delivery of therapeutic drugs to brain tumors.